Collecting duct NCOR1 controls blood pressure by regulating mineralocorticoid receptor - Ke Sun; Yong-Li Wang; Chen-Chen Hou; Da Shang; Lin-Juan Du; Lan Bai; Xing-Yu Zhang; Chuan-Ming Hao; Sheng-Zhong Duan (Journal of Advanced Research)
Introduction: Nuclear receptor corepressor 1(NCOR1) is reported to play crucial roles in cardiovascular diseases, but its function in the kidney has remained obscure. Objective: We aim to elucidate the role of collecting duct NCOR1 in blood pressure (BP) regulation. Methods and Results: Collecting duct NCOR1 knockout (KO) mice manifested increased BP and aggravated vascular and renal injury in an angiotensin II (Ang II)-induced hypertensive model. KO mice also showed significantly higher BP than littermate control (LC) mice in deoxycorticosterone acetate (DOCA)-salt model. Further study showed that collecting duct NCOR1 deficiency aggravated volume and sodium retention after saline challenge. Among the sodium transporter in the collecting duct, the expression of the three epithelial sodium channel (ENaC) subunits was markedly increased in the renal medulla of KO mice. Consistently, BP in Ang II-infused KO mice decreased significantly to the similar level as those in LC mice after amiloride treatment. ChIP analysis revealed that NCOR1 deficiency increased the enrichment of mineralocorticoid receptor (MR) on the promoters of the three ENaC genes in primary inner medulla collecting duct (IMCD) cells. Co-IP results showed interaction between NCOR1 and MR, and luciferase reporter results demonstrated that NCOR1 inhibited the transcriptional activity of MR. Knockdown of MR eliminated the increased ENaC expression in primary IMCD cells isolated from KO mice. Finally, BP was significantly decreased in Ang II-infused KO mice after treatment of MR antagonist spironolactone and the difference between LC and KO mice was abolished. Conclusions: NCOR1 interacts with MR to control ENaC activity in the collecting duct and to regulate sodium reabsorption and ultimately BP. Targeting NCOR1 might be a promising tactic to interrupt the volume and sodium retention of the collecting duct in hypertension.